ASSESSMENT OF POLLUTION-INDUCED DISSOLVED OXYGEN VARIATION IN RIVER CHALLAWA (Nigerian Journal of Technology, 2015)
The study is aimed at investigating the effect of industrial effluents on the water quality of River Challawa. Chemical analyses of samples of the river water collected at predetermined sampling points along a 10.644 km stretch were undertaken and the observations were subjected to ANOVA and regression analyses.The results obtained indicated that the DO values ranged from 2.4 mg/l to 1.9 mg/l, while the BOD5 ranged from 443 mg/l to 1654 mg/l; the COD ranged from 1296 mg/l to 4565 mg/l. The self-purification factor (f) for the River Challawa varies between 0.40 per day and 0.56 per day which puts the river in the sluggish stream category and as a heavily polluted stream. The predictions indicated significant relationship with the observed values at 95% level of significance.  http://dx.doi.org/10.4314/njt.v34i3.27